Segment 4 and the left lateral segment regeneration pattern after resection of the middle hepatic vein in a living donor right hepatectomy. Issue 1 (11th September 2014) - Lubezky, Nir; Oyfe, Irina; Contreras, Alan G; Rocca, Juan P; Rudow, Dianne LaPointe; Keegan, Tara; Taouli, Bashir; Kim‐Schluger, Leona; Florman, Sander; Schiano, Thomas; Facciuto, Marcelo
Abstract Background Inclusion of the middle hepatic vein (MHV) with a right hepatectomy (RH) in live donor liver transplantation improves venous drainage of the anterior sector of the graft. Its long‐term effects on donor left liver (LL) regeneration are not well described. Methods Donors who underwent RH with MHV (MHV+, n = 12) were compared with donors who underwent RH with preservation of the MHV (MHV–, n = 24). Peri‐operative complications and volume of the entire liver and individual segments were evaluated at 1 year post‐donation. Results There was a trend towards a higher complication rate in the MHV+ group (41% versus 25%), without reaching statistical significance (P = 0.3). Males, high body mass index (BMI) and a smaller residual liver volume (RLV) were predictors for greater LL regeneration. MHV+ donors had impaired regeneration of segment 4 (S4) at 1 year, and compensatory greater left lateral segment regeneration. The absence of venous drainage of S4 (V4) to left hepatic vein (LHV) was a predictor of impaired S4 regeneration. Conclusions Regeneration of S4 is impaired in MHV+ donors. Caution should be taken when considering MHV removal on donors with dominant S4, especially on those with potential increased demand for liver regeneration, such as males, higher BMI and a smaller RLV.